ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI PADI SAWAH DI KELURAHAN SISIPAN KECAMATAN BATUI KABUPATEN BANGGAI - Moh. Wahyudi J. Bolong; Dian Puspapratiwi; Irsan Z Tatu; Trianto Enteding (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2023)
The main activities and main sources of income of the community, especially people in rural areas, are still dependent on the agricultural sector.  An agricultural commodity that is expected to move positively in terms of increasing production and income is rice. The purpose of this study is to find out what factors affect the production of paddy rice farming in Sisipan Village, Batui District. Knowing how much production and income of paddy rice farming is in Sisipan Village, Batui District.  The results obtained from this study are the Use of Production Inputs and Production Factors studied, 5 variables affect paddy rice production, namely land area (X1), seed use (X2), fertilizer use (X3), pesticide use (X4), and labor use (X5).  Based on the income analysis, the average respondent farmer revenue rate was Rp. 24,022,857.14 with costs incurred by respondent farmers for the production process of paddy rice farming business on average Rp. 4,004,452.38, so that the average income of paddy rice farming by respondent farmers was Rp. 20,018,404.76.